RETROSPECTIVE ANALYSIS OF CASES OF UNDEVELOPED PREGNANCY IN WOMEN WITH COVID-19 - Ruzmetova , N.F. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. An undeveloped pregnancy is an important problem for women’s health, and its risk may be increased during pregnancy. Pregnant women with COVID-19 may have an increased risk of developing an undeveloped pregnancy. The purpose of this study is to conduct a retrospective analysis of cases of undeveloped pregnancy in women with COVID-19. Materials. The study used medical records of those who had an undeveloped pregnancy in the period from December 2020 to June 2021. A retrospective analysis of medical documentation was performed to assess cases of undeveloped pregnancy in women with COVID-19. The data were obtained from medical records and databases of patients in the archive of obstetric complex No. 9.Tashkent. The case histories were analyzed in the archive of the obstetric complex Results. Out of 100 women who had an undeveloped pregnancy during COVID-19, all women had confirmed COVID-19 infection, of which 35 women (35%) had a mild form of COVID-19 and 65 women (65%) had a severe form of coronavirus infection. Among women with an undeveloped pregnancy, 57 (57%) were infected with COVID-19 in the first trimester of pregnancy, 43 (43) - in the second trimester. Non–developing pregnancy was more often observed at the terms of 5 to 16 weeks, of which at 5-8 weeks - 41%, at 9-12 weeks.-30% and 13-16 weeks - 29%. Conclusion. A retrospective analysis of cases of non-developing pregnancies in women with COVID-19 highlights the potential impact of viral infection on pregnancy outcomes. A study has shown that COVID-19 infection can increase the risk of non-developing pregnancy in women, especially in the first trimester. The findings highlight the importance of timely and appropriate management of pregnant women with COVID-19 to minimize the risk of adverse pregnancy outcomes. Stress, hemostasiological and immunological disorders, as well as somatic diseases are important factors affecting the likelihood of an undeveloped pregnancy against the background of COVID-19.